2019
DOI: 10.2147/jbm.s204848
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effective method of evaluating myocardial iron concentration in pediatric patients with thalassemia major</p>

Abstract: Background The use of T2* magnetic resonance imaging (MRI) has been promoted by recent studies as a noninvasive method for the detection of iron overload in thalassemia major patients. This study aims to estimate the iron load in the heart and liver of thalassemia major patients using T2* MRI and to determine its correlation with the left ventricle ejection fraction and serum ferritin level. Methods Forty β-Thalassemia major patients were included in the study. We evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
(36 reference statements)
2
6
0
Order By: Relevance
“…Khaled et al. 15 also reported that the serum ferritin level was significantly negatively correlated with the cardiac T2* time but not with the hepatic T2* time in pediatric patients similar to those in our study. Yang et al.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Khaled et al. 15 also reported that the serum ferritin level was significantly negatively correlated with the cardiac T2* time but not with the hepatic T2* time in pediatric patients similar to those in our study. Yang et al.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, there was no significant correlation between these times, which can be explained by the small number of patients in our study. Khaled et al 15 also reported that the serum ferritin level was significantly negatively correlated with the cardiac T2* time but not with the hepatic T2* time in pediatric patients similar to those in our study. Yang et al 16 described the possibility of cardiac siderosis in pediatric patients with thalassemia as young as 6 years of age in cases of poorly effective chelation therapy.…”
Section: Discussionsupporting
confidence: 90%
“…The T2-weighted MRI (T2 MRI) criteria for cardiac iron overload were as follows: normal >20 milliseconds (ms), mild: 14-20 ms, moderate: 10-14 ms, and severe <10 ms. The T2 MRI criteria for hepatic iron overload were as follows: normal >6.3 milliseconds (ms), mild: 2.8-6.3 ms, moderate: 1.4-2.7 ms, severe <1.4 ms [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Serum ferritin level cannot be used as an indicator of myocardial iron overload, because it not only depends on several affecting factors such as hormonal system, 21,22 metabolic syndrome, 23 infection, 24 renal disease 25 and liver disease 26 but also have a weak correlation with myocardial MRI T2*, 27,28 especially in the elderly 29 . Consequent to the mentioned causes, as the serum ferritin level also rises, its assessment cannot be considered an accurate predictor for body iron burden in this population 28,30 . Importantly, a reduced level of serum ferritin does not deny the possibility of iron overload‐induced cardiomyopathy 16 …”
Section: Discussionmentioning
confidence: 99%